Forming Students’ Listening Comprehension Skills Through Artificial Intelligence Technologies - M.H. Azimova (LPPM STIE KRAKATAU, 2026)
Purpose: This study examines the role of Artificial Intelligence (AI) technologies in enhancing students’ listening comprehension skills in language learning. It focuses on the use of AI-powered tools, adaptive learning platforms, speech recognition systems, intelligent tutoring systems, and personalized educational applications to develop listening abilities. Research Methodology: A qualitative and literature-based approach was employed, analyzing scholarly articles, case studies, and educational reports on AI applications in language learning. The study synthesizes findings on the effectiveness, advantages, challenges, and pedagogical implications of AI integration in listening comprehension. Results: AI technologies create interactive, adaptive, and individualized learning environments that facilitate improved listening comprehension. Features such as real-time feedback, personalized content, and speech recognition significantly enhance students’ engagement, motivation, and skill acquisition. However, challenges including technological access, content quality, and teacher preparedness were identified as potential barriers to effective implementation. Conclusions: Integrating AI into language learning substantially supports the development of listening skills, fostering learner autonomy and providing tailored instructional experiences. Pedagogical strategies should emphasize combining AI tools with human-guided instruction to maximize learning outcomes. Limitations: The study relies primarily on literature review and secondary data, lacking empirical classroom-based validation. Findings may not fully generalize across different educational contexts, language proficiency levels, or regional technological availability. Contribution: This study provides a synthesized overview of AI applications in listening comprehension, offering practical insights for educators, curriculum designers, and policymakers on leveraging technology to enhance language learning outcomes.